2017
DOI: 10.1016/j.pneurobio.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the development of therapeutics for narcolepsy

Abstract: Narcolepsy is a neurological disorder that afflicts 1 in 2000 individuals and is characterized by excessive daytime sleepiness and cataplexy—a sudden loss of muscle tone triggered by positive emotions. Features of narcolepsy include dysregulation of arousal state boundaries as well as autonomic and metabolic disturbances. Disruption of neurotransmission through the hypocretin/orexin (Hcrt) system, usually by degeneration of the HCRT-producing neurons in the posterior hypothalamus, results in narcolepsy. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 324 publications
(466 reference statements)
0
46
0
4
Order By: Relevance
“…Because cataplexy occurrence varies widely between narcolepsy models (e.g., Veh groups in Figure 5A-D ) as well as among mice of the same genotype (46), data from Alm-pretreated Atax mice and DTA Dox(−) mice were pooled to assess correlations between cataplexy density (number of cataplexy bouts per minutes awake) after Veh vs. the therapeutic change from Veh post-dosing with RO5263397 (0.3-3 mg/kg), RO5256390 (1-10 mg/kg) and Des (5 mg/kg) ( Figure 5E-F ). Pearson product-moment correlations revealed that, as basal cataplexy levels increased (measured as cataplexy density after Veh treatment), cataplexy density after drug treatment decreased for RO5263397 (0.3, 1, 3 mg/kg) ( r (14)=−0.89, −0.62, −0.77, respectively, all P <0.01), RO5256390 (1, 3, 10 mg/kg) ( r (14)=−0.97, −0.74, −0.82, respectively, all P <0.01) and Des (5 mg/kg) ( r (14)=−0.92, P <0.01).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because cataplexy occurrence varies widely between narcolepsy models (e.g., Veh groups in Figure 5A-D ) as well as among mice of the same genotype (46), data from Alm-pretreated Atax mice and DTA Dox(−) mice were pooled to assess correlations between cataplexy density (number of cataplexy bouts per minutes awake) after Veh vs. the therapeutic change from Veh post-dosing with RO5263397 (0.3-3 mg/kg), RO5256390 (1-10 mg/kg) and Des (5 mg/kg) ( Figure 5E-F ). Pearson product-moment correlations revealed that, as basal cataplexy levels increased (measured as cataplexy density after Veh treatment), cataplexy density after drug treatment decreased for RO5263397 (0.3, 1, 3 mg/kg) ( r (14)=−0.89, −0.62, −0.77, respectively, all P <0.01), RO5256390 (1, 3, 10 mg/kg) ( r (14)=−0.97, −0.74, −0.82, respectively, all P <0.01) and Des (5 mg/kg) ( r (14)=−0.92, P <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Suppression of REM sleep is a characteristic of many anticataplectic medications (46). Although both RO5263397 and RO5256390 were effective in reducing cataplexy, RO5263397 was more effective in reducing REM sleep in the Atax narcolepsy model ( Figure 3I ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like their human counterparts, Atax mice experience degeneration of wakepromoting orexin (also known as hypocretin) neurons which leads to cataplexy (a sudden, reversible loss of muscle tone and REM-sleep like EEG) and/or increased sleep propensity at times of day when wakefulness would otherwise predominate (18). Although Atax mice exhibit cataplexy that is readily identifiable according to EEG/EMG-dependent consensus criteria (19), high inter-individual variability in cataplexy occurrence presents a challenge to sort mice for inclusion in studies with cataplexy reduction as an endpoint (20). Currently, there is no prescreening method prior to EEG/EMG studies for sorting mice that are highly symptomatic for narcolepsy.…”
Section: Introductionmentioning
confidence: 99%